2002
DOI: 10.1016/s0008-6363(02)00326-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia and endothelial loss on vascular smooth muscle cell responsiveness to VEGF-A: role of flt-1/VEGF-receptor-1

Abstract: These findings demonstrate that experimental conditions mimicking pathological vascular injury can make VSMCs responsive to VEGF-A through the induction of functional flt-1 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 26 publications
3
57
0
Order By: Relevance
“…PAI-1 and TGF-β interfere with liver regeneration by suppressing hepatocyte growth factor (38). Although VEGF-A usually acts as a vasodilator, it can act as a vasoconstrictor under conditions of endothelial failure and hepatic sinusoidal injury (39). Platelet aggregation in the space of Disse may explain many of the symptoms, venous perfusion abnormalities, and portal hypertension detected in SOS, findings that cannot be confirmed pathologically.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 and TGF-β interfere with liver regeneration by suppressing hepatocyte growth factor (38). Although VEGF-A usually acts as a vasodilator, it can act as a vasoconstrictor under conditions of endothelial failure and hepatic sinusoidal injury (39). Platelet aggregation in the space of Disse may explain many of the symptoms, venous perfusion abnormalities, and portal hypertension detected in SOS, findings that cannot be confirmed pathologically.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 and TGF-β interfere with liver regeneration by suppressing hepatocyte growth factor (21). VEGF-A, which usually acts as a vasodilator, may paradoxically act as a vasoconstrictor under conditions of endothelial failure (22). Moreover, bevacizumab, an antibody against VEGF-A, was found to protect against SOS in patients administered oxaliplatin-based chemotherapy for CRLM (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a specific mitogen for endothelial cells, whose up-regulated expression under hypoxic conditions is necessary for the neoangiogenesis of endothelial cells 17,18) . Recently, it was reported that in cultured rat VSMCs, hypoxia induced the upregulation of VEGF-A mRNA expression, and enhanced VEGF-induced cell proliferation 10) . PDGF is reported to stimulate the proliferation of VSMCs and to be involved in vascular remodeling 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the anti-PDGF antibody slightly inhibited the incorporation of thymidine at 12 h under hypoxic conditions (data not shown). Parenti et al showed that PDGF is not significantly effective in promoting rat VSMCs growth 10) . Humar et al 21) demonstrated that the mammalian target of rapamycin (mTOR) is involved in hypoxia-triggered proliferation of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation